Students’ persistence intention in MOOCs in the psychomotor domain: An extended 3P model of the teaching and learning perspective - Yang, Hsi-Hsun; Lin, Jia-Yu (Frontiers in Psychology, 2023)
This study proposed and tested a model adapted from Biggs’ 3P model that quantifies the behaviors of students who completed MOOCs (Massive Open Online Courses) in order to design intervention measures for low retention rates. Psychomotor domain data from 300 MOOC learners was analyzed in a covariance-based structural equation model (CB-SEM) to analyze the direct and indirect effects of various factors. Results show the basic psychological needs theory (BPNT) in the presage stage significantly positively correlated with engagement in the process stage. Meanwhile, the process stage exhibited a significantly positive correlation with the product stage, representing persistence intention (PI). Furthermore, a full mediation effect was observed among the presage, process, and product stages. The mediating effect demonstrates that higher student engagement leads to more positive exertion on BNPT and PI to complete the course. Moreover, results show bolstering students’ behavioral, emotional, and cognitive engagement strengthens their PIs.